Pengaruh Migrasi, Modal Manusia dan Investasi Asing Terhadap Ketimpangan Pendapatan di Indonesia - Dian Nofita Zola; Yeniwati Yeniwati (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
The results of this research explain that as long as there are influences betweenmigration, human capital, foreign investment on income inequality inIndonesia. This research is a combination of cross section and time series using33 provinces and from 2013 – 2019, using the panel regression method and thefixed effect model selection test. The results of the research prove that: (1)Migration has a significant positive effect on income inequality in Indonesia,(2) Human capital has a negative and significant effect on Income Inequality inIndonesia, (3) Foreign Investment has a not significant positive effect onIncome Inequality in Indonesia.